Parity Frontiers in Urban Delivery: A Route Level Cost to Serve Framework with Evidence from Europe and Southeast Asia - Sucipto, Purwo Agus (Novatio : Journal of Management Technology and Innovation, 2023)
Last mile delivery represents a significant share of logistics spending, yet investment decisions often rely on fleet-average costs. This study examines the conditions under which battery electric light commercial vans (BEVs) achieve lower cost-to-serve (CTS) per stop than internal combustion engine (ICE) vans, focusing on the role of charging strategies and urban operating environments. An activity-based framework is applied to decompose CTS into energy, maintenance, and labor, calibrated using urban, mixed, and suburban route archetypes under 2023 price conditions. Three charging strategies overnight depot alternating current, mixed alternating and direct current fast charging, and full reliance on public fast charging are evaluated through sensitivity analysis and Monte Carlo simulations, with external validation in Indonesia and Southeast Asia. Findings show that BEVs consistently deliver lower CTS than ICE vans across scenarios. Savings are modest in dense cores dependent on public fast charging but substantial on suburban routes with reliable overnight depot charging. While labor dominates total CTS, energy and maintenance determine the direction of parity, and off-peak tariffs significantly expand BEV advantages. In Southeast Asia, BEVs remain favorable when operators access predictable off-peak supply and manage curb access, though diesel subsidies and grid constraints influence margins. The study concludes that electrification yields the greatest benefits when route design and charging strategies are aligned, and recommends integrating per-stop analysis with total cost of ownership to guide fleet investment and infrastructure planning.